Harmoni Filsafat dan Teologi dalam Pemikiran Thomas Aquinas: Kontribusi terhadap Pemahaman Kebenaran Ilahi - Andreas Ferdian Ginting; Mathias Jebaru Adon (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2024)
Thomas Aquinas' thoughts on the relationship between reason (intellect) and revelation (faith) play a crucial role in the tradition of Christian theology, particularly within the Catholic Church. Aquinas argued that reason and faith are two sources of knowledge that do not contradict each other but complement one another. He distinguished between scientific knowledge, which is acquired through reason and sensory experience, and knowledge of faith, which is rooted in divine revelation that transcends the capacity of human reason. According to Aquinas, while human reason can grasp certain divine truths, revelation is necessary to understand deeper and limitless truths, such as the mysteries of God and the Christian teachings found in sacred scripture. Aquinas' thought resulted in a synthesis between Aristotelian philosophy and Christian doctrine, where philosophy investigates the material world, while theology explores divine truths. Aquinas proposed that reason and revelation have distinct yet supportive roles in the pursuit of truth. This view provided a strong intellectual foundation for the Catholic Church and offered a solution to the tension between reason and faith. Aquinas' ideas remain relevant today, particularly in the dialogue between science and religion, which complement each other in the pursuit of a more holistic understanding of reality and human existence.